Higher Education, Nation Character, and Religious Moderation Program: A Public Policy Perspective - Tatang Sudrajat; Supiana Supiana; Qiqi Yuliati Zakiah (Journal of Asian Social Science Research, 2021)
The diversity of the Indonesian nation in terms of religion, ethnicity, race, local culture, and others is an inevitable reality. It constitutes the nation’s socio-cultural capital, wealth, and potential to advance in which Indonesia can be proud of. But, it can also lead to attitudes and behaviour that damage national integration. Attitudes and behaviour that are tolerant of differences, inclusive, and moderate, especially in religious life, are the main pillars of a strong nation. Currently, the attitudes and behaviour of certain groups of citizens and individuals show the opposite and these dominate the Indonesian public sphere. Using normative juridical methods and literature, this article examines the religious moderation program launched by the Indonesian government under the coordination of the Ministry of Religious Affairs as an effort to deal with the rising religious intolerance and violence in Indonesia. From a public policy perspective, this article aims to analyse actors that are involved in the religious moderation program initiated by the Ministry of Religious Affairs. Higher education institutions with their resources have the opportunity to support this program. The religious moderation program is an implication of the policy environment that is currently embedded in people's daily lives.